Upgrading rice husk via oxidative torrefaction: Characterization of solid, liquid, gaseous products and a comparison with non-oxidative torrefaction. (1st September 2020) - Chen, Dengyu; Chen, Fan; Cen, Kehui; Cao, Xiaobing; Zhang, Jie; Zhou, Jianbin
Highlights: Oxidative and non-oxidative torrefaction of rice husk were comparatively studied. Oxidation of hydrocarbons played an important role in thermal degradation of sample. Higher O2 concentration promoted the severity of torrefaction and formation of CO2 . The formation of water and acetic acid was promoted by the presence of O2 . O2 containing atmosphere could replace N2 atmosphere to reduce torrefaction cost. Abstract: In this study, oxidative torrefaction and non-oxidative torrefaction of rice husks were performed under different severities, and the effects of temperature (220–300 °C) and O2 concentration (0–15 vol%) on the properties of the solid, liquid, and gas products were investigated. Oxidation of hydrocarbons play an important role in thermal degradation of samples, and higher O2 concentration promotes the severity of torrefaction. Oxygen content in rice husk decreased whether the torrefaction temperature increased or the O2 concentration increased. Consequently, the H/C and O/C ratios as well as the mass and energy yield of the sample remarkably decreased, even at small O2 concentrations of 2%. Gas yield in the oxidative torrefaction process was higher than that in non-oxidative torrefaction. CO2 was the dominant gas, and volume fraction of CO2 further increased during oxidative torrefaction. This may be contributed to enhanced thermal degradation of rice husk and to the combustion reaction between CO and O2, especially at a higher torrefaction temperature and with a higher concentration of O2 . In the case of liquid products, acids and phenols were the dominant organic components. However, formation of water and acetic acid was promoted, whereas the presence of O2 inhibited generation of levoglucosan. On the basis of products distribution and the evaluation of O2 that participates in torrefaction, it was concluded that O2 -containing atmosphere could be a potential agent to replace a pure N2 atmosphere, which may reduce operational costs and make biomass torrefaction more commercially feasible.